Recapturing the Thought or the Pioneers: the Concept of Communication in the Sociological Theory of Robert E. Park (Communication & Society, 1999)
In the beginnings of mass Communications theory we find several authors, Robert E. Park among them, who were consigned to oblivion after the Second World War, at the very time when research on the effects of mass communication reached the height of its influence. In spite of the large cal work, very little has been written about the vital function he attributes to the concepts of communication, public opinion and the press. The present article considers the importance of the first of these ideas, communication, throughout his work.